2016
DOI: 10.1108/imds-04-2015-0116
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the service quality in the e-commerce context: a triadic view

Abstract: Purpose – The purpose of this paper is to explore the quality factors influencing customer satisfaction in the electronic commerce (e-commerce) context using a triadic view of customer-e-retailer-third-party logistics provider, and to investigate the impacts of service quality on customer satisfaction and loyalty in the e-retailing supply chain. Design/methodology/approach – A literature review is used to determine the conceptual model a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
64
1
12

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(93 citation statements)
references
References 81 publications
16
64
1
12
Order By: Relevance
“…Stopka et al (2016) argued that CS is very important for logistics companies seeking a competitive advantage because if they do not meet the expectations of their customers, this function will be assumed by other firms. The study by Lin et al (2016) on e-commerce firms in China showed that the quality of electronic service had a positive effect on CS. Nevertheless, the quality of their logistics service negatively affected CS.…”
Section: Cs Mediated By Lsq ─ Indirect Impactmentioning
confidence: 99%
“…Stopka et al (2016) argued that CS is very important for logistics companies seeking a competitive advantage because if they do not meet the expectations of their customers, this function will be assumed by other firms. The study by Lin et al (2016) on e-commerce firms in China showed that the quality of electronic service had a positive effect on CS. Nevertheless, the quality of their logistics service negatively affected CS.…”
Section: Cs Mediated By Lsq ─ Indirect Impactmentioning
confidence: 99%
“…Third, the physical fulfilment can help to increase consumers' satisfaction in the delivery of goods and services. Lin et al (2016) delivered a study to investigate the impacts of physical fulfilment service quality on consumer satisfaction using a triadic view of consumer-online-store-3PL.…”
Section: Multinational Enterprisesmentioning
confidence: 99%
“…A significant number of researches was delivered in this area. These criteria range from website design, effectiveness and efficiency of online browsers (information availability and search function) (Tucker, 2008), security issues (Lin et al, 2016). For example, Ramanathan (2010) defines efficiency towards e-commerce websites as their ability to achieve the right presence in terms of operational factors and customer loyalty (Ramanathan, 2010).…”
Section: Multinational Enterprisesmentioning
confidence: 99%
“…Among the scientific papers combining the topics of e-commerce and supply chains, there are mainly studies that raise the subject of logistics customer service (Lin, Luo, Cai, Ma, & Rong, 2016), challenges of the logistics industry related to the dynamic growth of online sales (Joong- Kun Cho, Ozment, & Sink, 2008) and studies that deal with the behavioral and marketing issues connected to the creation of virtual sales channels (including cultural, economic and political conditions) (Lawrence & Tar, 2010). However, there are no articles in which the impact of supply chain types on the ability to create virtual sales channels with the support of smart solutions is considered.…”
Section: Introductionmentioning
confidence: 99%